Al-Istifādah min al-Lahjah al-Ḥijāziyyah fī Tadrīs al-Asālīb al-Naḥwiyyah li al-Nāṭiqīn bi Ghairi al-‘Arabiyyah - Saadah Munaf; Ahmad Muradi; Faisal Mubarak; Fatwiah Noor (Lughawiyyat: Jurnal Pendidikan Bahasa dan Sastra Arab, 2021)
Abstract Arabic language is characterized by the diversity of expression methods, and has characteristics and advantages that must be taken into account, as it is a multi-system that differs according to the location of the sentence, the form and the event. Grammar methods are a pivotal part of learning Arabic, especially in speaking skill, as Arabic conversations are full of stylistic contexts in which we employ these methods that, if we know them, we know the entire language. The researcher of this research aims to: (1) identify the intersections between Hijaz dialect and al-Fusha (2) explore how to gain benefits from the intersections in teaching grammatical methods when teaching the skill of speaking. The researchers followed the descriptive analytical approach. The sources of data that the researchers relied upon were books, documents, journals and scientific dissertations, research papers, and Arabic dictionaries and the interview. The most important results of the research were:(1)The grammatical methods came in the same way with the Hijaz dialect and al-fusha, with some difference in controlling the structure and the syntactic movement.(2)The use of the Hijaz dialect in teaching these methods to approximate the classical Arabic appears possible in light of the intersections between them, especially for non-speakers who lived with Arabs and bring benefit within the limits of clarifying the function that the method performs within the verbal context, and represents a functional trend in teaching Standard Arabic, because it depends on the function that the method performs in not controlling the syntactic form. Keywords: Hijaz Dialect, Arabic Language, Grammatical Methods